The Relationship Between Inflammation and Post-traumatic Stress Disorder - Sun, Yajing; Qu, Yuanyuan; Zhu, Jianwei (Frontiers in Psychiatry, 2021)
Background: Stress disorders, such as post-traumatic stress disorder (PTSD), are attracting much attention. However, the relationship between traumatic stress and inflammation is rarely discussed. Subjects and Methods: As studies have linked PTSD to altered susceptibility to various diseases, such a psychiatric condition may lead to long-term systematic changes in physiological functions. We searched PubMed with the keywords “traumatic stress,” “stress disorders,” “post-traumatic stress disorder,” and “inflammation.” Results: Based on 65 previously published studies, we reviewed the long-term effects of PTSD, as well as traumatic events, on inflammatory function from both epidemiological and biological perspectives. Post-traumatic stress disorder is related to the immune response, including an increase in inflammatory factors and a reduction in anti-inflammatory factors. Additionally, it has been demonstrated that traumatic stress disorder and immune disease share a common genetic basis at the gene expression level. Conclusions: Understanding this relationship is of great significance for optimizing treatment plans for patients with PTSD.